Science process skills structure and activity of inorganic compounds reviewing from knowledge of prospective chemistry teachers - Fitriani, Henni; Mellyzar, M; Rahmi, Ayu (International Journal for Educational and Vocational Studies, 2022)
The purposes of this study is to make it easier for students to understand a material and improve students' process skills, thus making students more interactive. The learning process is carried out in groups, interactively, formulates problems, and evaluates gaps in their knowledge, studies and searches for materials related to problems and solutions to these problems. Then students can ask questions, and determine answers to questions that are excluded from everyday experience. Then they also have the ability to describe, explain and predict natural phenomena in the structure and reactivity of inorganic compounds. This study is a quantitative-research with pre-experimental One-Shot Case Study research with the research target of 7th semester students of chemistry education study program who are prospective chemistry teachers. This study uses a rubric test in the form of description questions. The results showed that the results of students' sciences process skills on the structure and reactivity of inorganic compounds had reached the percentages obtained by students on the criteria of observing, classifying, measuring, communicating, predicting, and drawing verbal conclusions, namely 87.50%, 88.75 %, 83.75%, 93.75%, 85%, and 91.25%. So that the average percentage of these criteria is 87.75% with a score of 3.51. With the results obtained, prospective chemistry teachers can improve the learning of science process skills and increase mastery of basic concepts of inorganic chemistry, especially on the material structure and reactivity of inorganic compounds.